The First Legai Document from the Later Old Assyrian Period - Gelb, I. J.
1. Introduction — 2. Description: Tablet and Envelope — 3. Transliteration and Transcription — 4. Translation — 5. Notes to the Transliteration and Translation — 6. Content of the Text — 7. Date and Place of Origin.